2011
DOI: 10.1186/1471-2458-11-s3-s19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multiple micronutrient supplementation during pregnancy on maternal and birth outcomes

Abstract: Objectives/backgroundGiven the widespread prevalence of micronutrient deficiencies in developing countries, supplementation with multiple micronutrients rather than iron-folate alone, could be of potential benefit to the mother and the fetus. These benefits could relate to prevention of maternal complications and reduction in other adverse pregnancy outcomes such as small-for-gestational age (SGA) births, low birth weight, stillbirths, perinatal and neonatal mortality. This review evaluates the evidence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
86
2
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 40 publications
6
86
2
2
Order By: Relevance
“…5 In 2011, an estimated 165 million children aged ,5 years worldwide had stunted growth, with the majority residing in Asia and sub-Saharan Africa. 6 Prenatal multiple micronutrient (MMN) 7 and balanced energy and protein 8 supplementation result in a significant reduction in small-for-gestational age births (9% and 31%, respectively). However, the results of such interventions on postnatal growth yielded more dispersed results.…”
mentioning
confidence: 99%
“…5 In 2011, an estimated 165 million children aged ,5 years worldwide had stunted growth, with the majority residing in Asia and sub-Saharan Africa. 6 Prenatal multiple micronutrient (MMN) 7 and balanced energy and protein 8 supplementation result in a significant reduction in small-for-gestational age births (9% and 31%, respectively). However, the results of such interventions on postnatal growth yielded more dispersed results.…”
mentioning
confidence: 99%
“…The impact of this intervention in another review by Imdad et al, showed no impact on stillbirths (RR 0.98; 95% CI: 0.88 to 1.10) [135] or on perinatal mortality (RR 1.07; 95% CI: 0.92 to 1.25) [135]. There was also no evident reduction in the risk of neonatal mortality (RR 1.05; 95% CI: 0.92 to 1.19) [134].…”
Section: Multiple Micronutrient Supplementationmentioning
confidence: 93%
“…However, the same review showed a significant reduction in the risk of SGA infants with the use of multiple micronutrient supplements (RR 0.91; 95% CI: 0.86 to 0.96) compared to iron-folate supplementation [134]. The impact of this intervention in another review by Imdad et al, showed no impact on stillbirths (RR 0.98; 95% CI: 0.88 to 1.10) [135] or on perinatal mortality (RR 1.07; 95% CI: 0.92 to 1.25) [135].…”
Section: Multiple Micronutrient Supplementationmentioning
confidence: 97%
See 1 more Smart Citation
“…13,14 In recent years in addition to the aforementioned issues of poor uptake and reach of IFA supplementation programmes, two factors have emerged, which suggest that the policy for isolated IFA supplementation in pregnancy ought to be reviewed. The first is the recognition that many women of reproductive age and pregnant women have multiple micronutrient (MMN) deficiencies [15][16][17][18] and the other is that in addition to anaemia, important birth outcomes such as LBW should be considered.Although an earlier meta-analysis of iron folate supplementation in pregnancy did not suggest a significant improvement in birthweight, 19 21 Others have indicated that IFA supplementation was associated with a significant reduction in early neonatal mortality by 47% in Indonesia 22 and that the combination of iron folate supplementation and IFA and IPTp (intermittent preventive treatment of plasmodium malaria) was associated with 24% reduction on neonatal mortality in 19 sub-Saharan African countries. …”
mentioning
confidence: 99%